IMPLEMENTASI LESSON STUDY PADA MATA KULIAH KETERAMPILAN LANJUTAN SEPAKBOLA UNTUK MENINGKATKAN KUALITAS PBM DAN PENGEMBANGKAN KARAKTER DISIPLIN, KEPEDULIAN, DAN FAIR PLAY - Subagio lrianto (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
Lesson study conducted by a team of custodian I teaching courses of Nikken UNY football aims to repair and improve the quality of learning advanced soccer skills courses, so it is expected to achieve competence. Learning through cooperative learning is implemented through football competition in advanced soccer skills course. Formation of the value of discipline, caring and fair play can be embedded to the students so that it becomes something usual behavior everyday and into the character of students. Lesson study can fix the lecture advanced soccer skills. Keywords: Lesson Study, PBM quality, disciplined, caring, fair play